2011
DOI: 10.1128/mcb.05244-11
|View full text |Cite
|
Sign up to set email alerts
|

QKI-Mediated Alternative Splicing of the Histone Variant MacroH2A1 Regulates Cancer Cell Proliferation

Abstract: The histone variant macroH2A1 contains a carboxyl-terminal ϳ30-kDa domain called a macro domain. MacroH2A1 is produced as one of two alternatively spliced forms, macroH2A1.1 and macroH2A1.2. While the macro domain of macroH2A1.1 can interact with NAD ؉ -derived small molecules, such as poly(ADP-ribose), macroH2A1.2's macro domain cannot. Here, we show that changes in the alternative splicing of macroH2A1 pre-mRNA, which lead to a decrease in macroH2A1.1 expression, occur in a variety of cancers, including test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
163
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(180 citation statements)
references
References 48 publications
11
163
0
2
Order By: Relevance
“…6A; Supplemental Table S4), and suggesting that breast and ovarian cancer use similar mechanisms for modifying the splicing patterns of tumor-associated ASEs. Consistently, an independent study using a large number of breast cancer tissues concluded that QKI expression is reduced in breast tumors (P-value <3.0 × 10 −3 , t-test) (Novikov et al 2011). In our hands, however, the most striking difference between tumor and normal breast tissues was not the change in global expression but rather in the pattern of QKI splicing ( Fig.…”
Section: Cancer-specific Splicing Factorsmentioning
confidence: 55%
See 1 more Smart Citation
“…6A; Supplemental Table S4), and suggesting that breast and ovarian cancer use similar mechanisms for modifying the splicing patterns of tumor-associated ASEs. Consistently, an independent study using a large number of breast cancer tissues concluded that QKI expression is reduced in breast tumors (P-value <3.0 × 10 −3 , t-test) (Novikov et al 2011). In our hands, however, the most striking difference between tumor and normal breast tissues was not the change in global expression but rather in the pattern of QKI splicing ( Fig.…”
Section: Cancer-specific Splicing Factorsmentioning
confidence: 55%
“…Closer examination of the effects of knocking down cancer-associated splicing factors on CSS ASEs revealed two groups of splicing factors. The first group includes core spliceosomal factors such as SNRPD2 (Schumperli and Pillai 2004) and SNRPG (Ma et al 2005), while the second includes alternative splicing regulators RBFOX2 (Sun et al 2012) and QKI (Novikov et al 2011). Both groups are underexpressed in the tumor microenvironment and modified the splicing of three out of five CSS ASEs in the SKOV3ip1 cell line (Fig.…”
Section: Cancer-specific Splicing Factorsmentioning
confidence: 99%
“…In this context, it is interesting to point out that melanoma cells are dedifferentiated cells that reactivate embryonic signaling pathways [54]. Others could point out functional differences between macroH2A1 splice variants in different types of cancer [55,56]. Ongoing and future studies are likely to reveal the importance, the regulation and the molecular function of macroH2A-containing epigenetic mechanisms in a larger number of physiological and pathological processes.…”
Section: Future Perspectivementioning
confidence: 99%
“…In the present study, the artificial altering of macroH2A expression was performed by the interference and overex- (25)(26)(27)(28)(29)(30). In these cancer types, the expression levels of macroH2A decreased significantly in tumor tissues compared with normal tissues.…”
Section: Discussionmentioning
confidence: 92%